Comparison The Effeciency of wild thyme leaf Extract (Oregano) as Natural Antioxidant in with some synthesized antioxidants - سوسن سعد , (Latakia University Journal -Biological Sciences Series, 2022)
This study has been done in order to study the influence of adding wild thyme leaf extract (ORG) as a natural antioxidant in Soybean Oil besides two synthesized antioxidants Butyl hydroxyl anyzol and Butyl hydroxyl toluene at different concentration ( 0.005, 0.01, 0.02, 0.04,)%, and its role to increase the shelf and to improve the properties of the Oil with the presence of control sample (with no additon). Oil properties were studied after being stored in both transparent and opaque bottles and exposed to the light for 120 days with aninter wals of 15 days This research showed significant effect of wild extract as antioxidant in oil samples, shelf life for all of the studied concentrations. An obvious increase in both pyroxid and acidity values and a decrease in iodine value were noticed. A positive impact of wild thyme leaf extract (ORG) was also noticed in keeping oil properties both in opaque bottles and transparent ones exposed to eight. Results revealed that wild thyme leaf extract shows higher activity as a natural antioxidant compared to those of synthesized antioxidants, at the studied concentrations.